ABOUT BUSINESS INTELLIGENCE IN THE CONTEXT OF CULTURAL-CIVILIZATIONAL WORLDS’ COMPETITION - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2024)
Confirmation in practice of the effectiveness of business intelligence led to a natural increase in interest in it, expanding the range of its forces and means. The growth of instrumental equipment for conducting business intelligence, as well as ways of identifying and countering, has increased the requirements for the level of professionalism and creativity, for mastery in the execution of “school”, “mandatory” and “free program”. The turning point of the transition period has added the possibility of expanding the role of consequences and the acuity of perception [1-5]. Today, the interests of not separate, individual corporations, but business networks united by strategic partnership and entire cultural-civilizational worlds collide more and more often in the competitive struggle. At the same time, individual (even key) production nodes can be located geographically very far from each other. At the same time, the peculiarities of the basic value-sense complexes of specific cultural-civilizational worlds in many cases determine not only the symbolic construction of identity, but also the stability of organizational structures in the clash of approaches; form their requirements for the balance of management actions in response, anticipation of changes. Moreover, the information revolution itself gives rise to new business models: both for internal use in corporations and for external communications with suppliers, consumers, and competitors, which significantly change the business world [6-12]. Timely receipt of information and its quality processing is increasingly becoming a critical resource. In particular, for example, the formation of global information networks provides prerequisites for monitoring economic activity and control over information traffic. Relying on global information and space systems of surveillance and business intelligence, the accumulation and analysis of global information becomes a powerful means of ensuring victory over a competitor, and manipulation of public consciousness (which forces countries concerned about the state of their information security to block the participation of the population in controlled by other centres of social networks, Internet, electronic communications). The maintenance of such competitive advantages is also solved through the development of information systems (information-in-warfare system), which guarantee an information advantage over the competitors. Emphasis on the information motive, as characteristic trait of today's level of business construction, forces organizational structures careful take into account the peculiarities of information flows, to adapt to them. The growing number of operations of concentric and conglomerate integration of units of indirect subordination, but included in the sphere of influence and / or strategic partnership (for example, due to the unity of goals, projects, etc.) is an increasingly noticeable component of the information resource.